OUTDOOR LEARNING ACTIVITY: IS IT EFFECTIVE TO ROUSE STUDENTS’ SPEAKING? - Indra Cahyono; Mutohhar Mutohhar (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The aim of this study was to investigate the effectiveness of outdoor learning activity in improving students speaking. 30 students were selected from 125 students of the third semester as the participants of the study. The design of the study was one group pre-test post-test quasi experimental design. The group was taught by outdoor activity. Then oral test was given in both pre and post-tests. The result of the test showed that the mean score of pre-test was 70.1 while the mean score of post-test was 79.5. Accordingly, the statistical analysis affirmed that outdoor learning activity was effective in improving the speaking ability of the students; another conclusion was that outdoor activity provided authentic material to the students where authentic material was very beneficial as it gave a valuable insight into a culture and language. More, outdoor environment included was potential to encourage meaningful learning by moving between the abstract and concrete as well as transforming experience into knowledge through reflection and communication Key words: outdoor learning activity, English speaking skill